Laying the foundation for a primary care core set of the International Classification of Functioning, Disability and Health (ICF) for community-dwelling older adults: A qualitative study - Johanna Tomandl; Stephanie Book; Anina Hoefle; Elmar Graessel; Cornel Sieber; Ellen Freiberger; Thomas Kuehlein; Susann Hueber; Susann Gotthardt (Medical Journals Sweden, 2021)
Objective: To explore relevant areas of functioning from the perspective of community-dwelling adults aged 75 years and over, in order to develop a Core Set of the International Classification of Functioning, Disability and Health (ICF) for community-dwelling older adults for use in primary care. Design: Qualitative study using semi-structured interviews and focus groups. Participants: A total of 27 community-dwelling older adults participated in the interviews and 24 of them in the focus groups. Methods: Following the proposed methodology of the ICF Research Branch, this is 1 of 4 preparatory studies in the Core Set development process. Within the transcripts, concepts of functioning were identified, based on Mayring's qualitative content analysis using deductive category assignment with the ICF being the category system. Results: Overall 6,667 concepts were identified. Most were linked to the Activities and Participation component. The most frequently identified categories were "recreation and leisure" and "family relationships". Conclusion: Categories from all ICF chapters were identified, demonstrating the complexity and multidimensionality of the ageing process, with a special emphasis on the component Activities and Participation. This qualitative study provides a list of relevant categories from the perspective of community--dwelling elderly people, which will be used to develop a Core Set for older primary care patients.